The Nation Fathers (Baballaret e kombit). Description and form of activities of Albanian political elites during First Balkan War - Czekalski, Tadeusz (Balcanica Posnaniensia. Acta et studia, 2012)
The process of creation of Albanian modern state had a crucial point in November 1912, during First Balkan War. The group of Albanian national activists from southern part of Albania and from some diaspora communities gathered in Vlora to proclaim independence of Albanian State. In the specific circumstances created by war, only a part of invited delegates could attend in Vlora meeting. The analysis of their age, profession and religious affilation showed significant differences in comparison with contemporary Albanian society. Majority of Albanian acitivists and insurgents (among them very influential Kosovo Albanians) was marginalised in the first phase of creation of Albanian state. The problem of representativeness of delegates in Vlora was one of the main obstacle in the cooperation of Albanians in the times of Principality of Albania (1912-1914).